Adventure-based training to promote physical activity and reduce fatigue among childhood cancer survivors: A randomized controlled trial. (July 2018) - Li, William H.C.; Ho, K.Y.; Lam, K.K.W.; Lam, H.S.; Chui, S.Y.; Chan, Godfrey C.F.; Cheung, A.T.; Ho, L.L.K.; Chung, O.K.
Abstract: Background: Cancer-related fatigue is one of the most distressing symptoms reported by childhood cancer survivors. Despite the body of evidence that regular physical activity helps alleviate cancer-related fatigue, insufficient participation in physical activity is frequently observed among childhood cancer survivors. Objectives: This study examined the effectiveness of an adventure-based training programme in promoting physical activity, reducing fatigue, and enhancing self-efficacy and quality of life among Hong Kong Chinese childhood cancer survivors. Design: A prospective randomised controlled trial. Settings: A paediatric oncology outpatient clinic, a non-governmental organisation, and a non-profit voluntary organisation. Participants: Hong Kong Chinese childhood cancer survivors aged 9–16 years who reported symptoms of fatigue and had not engaged in regular physical exercise in the past 6 months. Methods: The experimental group underwent a 4-day adventure-based training programme. The control group received a placebo intervention. The primary outcome was fatigue at 12 months. Secondary outcomes were physical activity levels, self-efficacy and quality of life at 12 months. Data collection was conducted at baseline, and 6 and 12 months after the intervention began. We performed intention-to-treat analyses. Results: From 6 January, 2014 to 8 June, 2015, we randomly assigned 222 eligible childhood cancer survivors to either an experimental (n = 117) or a control group (n = 105). The experimental group showed statistically significantly lower levels of cancer-related fatigue ( P  < 0.001), higher levels of self-efficacy ( P  < 0.001) and physical activity ( P  < 0.001), and better quality of life ( P  < 0.01) than the control group at 12 months. Conclusions: This study provides evidence that adventure-based training is effective in promoting physical activity, reducing cancer-related fatigue, and enhancing self-efficacy and quality of life among Hong Kong Chinese childhood cancer survivors. These results may help inform parents and healthcare professionals that regular physical activity is crucial for the physical and psychological wellbeing and quality of life of childhood cancer survivors.